2022
DOI: 10.1002/ijc.34389
|View full text |Cite
|
Sign up to set email alerts
|

The tumor microenvironment drives NK cell metabolic dysfunction leading to impaired antitumor activity

Abstract: NK cells represent key players capable of driving antitumor immune responses. However, the potent immunosuppressive activity of the tumor microenvironment (TME) may impair their effector function. Here, we strengthen the importance of metabolic interactions between NK cells and TME and propose metabolic dysfunction as one of the major mechanisms behind NK failure in cancer treatment. In particular, we described that TME has a direct negative impact on NK cell function by disrupting their mitochondrial integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…These metabolic dysfunctions were also induced in healthy donor pbNK cells when exposed to the TME 7 . Similarly, pbNK cells incubated with the malignant pleural effusion of patients with lung cancer have lower mitochondrial mass and function, and impaired OxPhos 17 . These mitochondrial defects were correlated with a reduced cytotoxic capacity of pbNK cells 17 .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…These metabolic dysfunctions were also induced in healthy donor pbNK cells when exposed to the TME 7 . Similarly, pbNK cells incubated with the malignant pleural effusion of patients with lung cancer have lower mitochondrial mass and function, and impaired OxPhos 17 . These mitochondrial defects were correlated with a reduced cytotoxic capacity of pbNK cells 17 .…”
Section: Introductionmentioning
confidence: 81%
“…7 Similarly, pbNK cells incubated with the malignant pleural effusion of patients with lung cancer have lower mitochondrial mass and function, and impaired OxPhos. 17 These mitochondrial defects were correlated with a reduced cytotoxic capacity of pbNK cells. 17 Overall, NK cell metabolism in a crucial factor in determining NK cell antitumor functions in the TME.…”
Section: The Metabolic Requirements Driving Nk Cell-mediated Tumor Ki...mentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells can exert tumoricidal function by releasing cytolytic granules and cytotoxic cytokines, which are controlled by a complex array of activating and inhibitory receptors. However, the metabolic impairment promotes the dysfunction of NK cells within TME. , To enhance the NK cell-mediated innate antitumor immunity by reprogramming its cellular metabolism, a immunosensitizer (BPQDs@HSA) was constructed by encapsulating black phosphorus (BP) quantum dots (QDs) in human serum albumin (HSA) (Figure A, Table ). In this study, the author found that the BPQDs@HSA treatment enhanced the expression of TLR-5, TLR-9, and NF-κB in NK cells (Figure B).…”
Section: Nanomedicines For Glucose Metabolism Interventionmentioning
confidence: 99%
“…In contrast, it is noteworthy that NK cells in cancer patients show impaired functions accompanied by a poor ability to infiltrate the tumor microenvironment (TME), as tumor cells adopt different various immune evasion mechanisms (10)(11)(12)(13)(14)(15)(16)(17). Therefore, the adoptive transfer of ex vivo expanded and activated allogeneic NK cells for immunotherapy turns out to be a strategic clinical adoption to help cancer patients to fight tumor cells, thus attracting increasing interest in the past decade (18).…”
Section: Introductionmentioning
confidence: 99%